Effectiveness of Behavioristic Counseling with Modeling Techniques to Minimize Cyberbullying Behavior in Students - Gunawan, I Made Sonny; Ahmad, Hariadi; Hartati, Aluh (Kuras Institute, 2024)
The aim of this research is to confirm the effectiveness of behavioristic counseling with modeling techniques in minimizing cyberbullying behavior carried out by students. This research uses a pretest-posttest control group design experimental approach. The subjects in this research were 8 students who attended State Senior High School 3 (SMA Negeri 3) Mataram. Data was collected using a Personality Scale in the form of a questionnaire developed based on indicators of cyberbullying behavior. Data analysis uses one-way Anova statistics. The results of this research reveal that behavioristic counseling using modeling techniques is effective in minimizing cyberbullying behavior. The forms of cyberbullying behavior that can be minimized well in this research are verbal cyberbullying behavior such as insulting behavior using bad words, and spreading rumors to embarrass one's friends.